Guia prático de acabamentos especiais: laminação e verniz UV para Corgraf - Pinto, Thais Ramos (2012)
This paper presents issues related to graphic production, printing processes and process of finishing a printing press in particular. The main objective was to research about the most popular special finishes of a graphical and report on both the processes and when we can use them, through a printed material that serves as a reference guide for designers, other interested agencies and other seller.